Magnitude of Child Sexual Abuse and Its Associated Factors Among Children Treated in Public Hospitals of Addis Ababa Ethiopia - Alemayehu B; Tafesse N; Chanyalew E (Adolescent Health, Medicine and Therapeutics, 2022)
Belayneh Alemayehu,1 Nebiyou Tafesse,2 Eden Chanyalew1 1Department of Nursing and Midwifery, Tirunesh Beijing General Hospital, Addis Ababa, Ethiopia; 2Department of Public Health, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Belayneh Alemayehu, Department of Nursing and Midwifery, Tirunesh Beijing General Hospital, Addis Ababa, Ethiopia, Tel +251920772457, Email belaynehalexel@gmail.comBackground: Child sexual abuse is a serious breach of basic human rights and is responsible for numerous adverse squeals and widespread global public health concern. The highest prevalence of child sexual abuse was seen in Africa. In Ethiopia, a study was conducted in Jimma town, and the study indicates that the prevalence of violence among high-school children was 62.5%. Despite this fact, it often remains unrecognized and unidentified. Thus, the aim of the study was to assess the magnitude of child sexual abuse and its associated factors among children treated in public hospitals of Addis Ababa, Ethiopia.Methods: An institutional-based cross-sectional quantitative design study was conducted on 422 children. Study participants were selected by systematic random sampling. The data were collected through a face-to-face interview. The data were analyzed by SPSS version 26. By considering a 95% confidence level and a P value of < 0.05, binary logistic regression was used to identify factors associated with child sexual abuse.Results: A total of 422 children participated. Among these, 42.7% of them experienced sexual abuse. Children older than 15 years were 2 times more likely to face sexual abuse than those whose age is less than 10 years [AOR = 2.27 (95% CI: 1.23– 4.19)]. Children who chew khat and smoke were abused more likely compared with their counterparts. The odds of having sexual abuse in a child with mental illness were six times more likely than children who do not have mental illness [AOR = 5.945 (95% CI: 1.642– 21.528)].Conclusion and Recommendations: The magnitude of child sexual abuse in Addis Ababa was high. Children age, sex, khat chewing, physical disability, mental illness, smoking, and alcohol use were factors associated with child sexual abuse. Children with mental illness and physical disabilities should be treated and supported with special attention.Keywords: child sexual abuse, associated factors, Addis Ababa, Ethiopia